TRACKING THE VALIDITY OF PROFESSION WAQF IN A POSITIVE LEGAL PERSPECTIVE IN INDONESIA - Athoillah Islamy; Doni Setiadi (Al-'Adl, 2020)
In realizing the benefit and social justice of waqf goals, efforts to innovate the management of waqf forms in Indonesia are inevitable. This study aims to find the legality of profession waqf in the review of the Waqf Law in Indonesia on the implementation of profession waqf. This type of research is literature review. Meanwhile, the type of legal research approach in this research is normative legal research. The source of this research data in the form of a variety of literature that explains the concept of profession waqf. While the knife analysis used in this study, namely Law Number 41 of 2004, Compilation of Islamic Law (KHI) and Government Regulation Number 28 of 1977. This study concludes two big conclusions. First, profession waqf is a form of innovation of  waqf instruments aimed at increasing the benefit of waqf for public benefit. Second, the existence and purpose of profession waqf is in line with positive law in Indonesia which explains that waqf aim at the general welfare by utilizing the potential and economic value of waqf